Common genetic variation in alcohol-related hepatocellular carcinoma: a case-control genome-wide association study. Issue 1 (January 2022) - Trépo, Eric; Caruso, Stefano; Yang, Jie; Imbeaud, Sandrine; Couchy, Gabrielle; Bayard, Quentin; Letouzé, Eric; Ganne-Carrié, Nathalie; Moreno, Christophe; Oussalah, Abderrahim; Féray, Cyrille; Blanc, Jean Frédéric; et al.
Summary: Background: Hepatocellular carcinoma is a frequent consequence of alcohol-related liver disease, with variable incidence among heavy drinkers. We did a genome-wide association study (GWAS) to identify common genetic variants for alcohol-related hepatocellular carcinoma. Methods: We conducted a two-stage case-control GWAS in a discovery cohort of 2107 unrelated European patients with alcohol-related liver disease aged 20–92 years recruited between Oct 22, 1993, and March 12, 2017. Cases were patients with alcohol-related hepatocellular carcinoma diagnosed by imaging or histology. Controls were patients with alcohol-related liver disease without hepatocellular carcinoma. We used an additive logistic regression model adjusted for the first ten principal components to assess genetic variants associated with alcohol-related hepatocellular carcinoma. We did another analysis with adjustment for age, sex, and liver fibrosis. New candidate associations (p<1 × 10 −6 ) and variants previously associated with alcohol-related hepatocellular carcinoma were evaluated in a validation cohort of 1933 patients with alcohol-related liver disease aged 29–92 years recruited between July 21, 1995, and May 2, 2019. We did a meta-analysis of the two case–control cohorts. Findings: The discovery cohort included 775 cases and 1332 controls. Of 7 962 325 variants assessed, we identified WNT3A-WNT9A (rs708113; p=1·11 × 10 −8 ) and found support for previously reported regions associated with alcohol-related hepatocellular carcinoma risk at TM6SF2 (rs58542926; p=6·02 × 10 −10 ), PNPLA3 (rs738409; p=9·29 × 10 −7 ), and HSD17B13 (rs72613567; p=2·49 × 10 −4 ). The validation cohort included 874 cases and 1059 controls and three variants were replicated: WNT3A-WNT9A (rs708113; p=1·17 × 10 −3 ), TM6SF2 (rs58542926; p=4·06 × 10 −5 ), and PNPLA3 (rs738409; p=1·17 × 10 −4 ). All three variants reached GWAS significance in the meta-analysis: WNT3A-WNT9A (odds ratio 0·73, 95% CI 0·66–0·81; p=3·93 × 10 −10 ), TM6SF2 (1·77, 1·52–2·07; p=3·84×10 −13 ), PNPLA3 (1·34, 1·22–1·47; p=7·30 × 10 −10 ). Adjustment for clinical covariates yielded similar results. We observed an additive effect of at-risk alleles on alcohol-related hepatocellular carcinoma. WNT3A-WNT9A rs708113 was not associated with liver fibrosis. Interpretation: WNT3A-WNT9A is a susceptibility locus for alcohol-related hepatocellular carcinoma, suggesting an early role of the Wnt–β-catenin pathway in alcohol-related hepatocellular carcinoma carcinogenesis. Funding: Ligue Nationale contre le Cancer, Bpifrance, INSERM, AFEF, CARPEM, Labex OncoImmunology, and Agence Nationale de la Recherche.